Investigation of the relationship between genetic and environmental risk factors associated with obesity and insulin resistance in South African patients with non-alcoholic fatty liver disease(NAFLD) - Pretorius, Jakobus (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSCMedSc)--Stellenbosch University, 2012.